Abstract Number ‐ 142: Flow Diversion for Posterior Communicating Artery Aneurysms: Systematic Review and Meta‐Analysis - Juan Vivanco‐Suarez; Aaron Rodriguez‐Calienes; Mudassir Farooqui; Milagros Galecio‐Castillo; Marco Malaga; Satiago Ortega‐Gutierrez (Stroke: Vascular and Interventional Neurology, 2023)
Introduction Posterior communicating artery (PComA) aneurysms are common and have a high risk of rupture. Flow diverters (FD) have demonstrated a safe and effective profile. However, the use of FD in PComA aneurysms has shown controversial results with high rates of recurrence and a high risk of potential ischemic complications. There, we aimed to evaluate the safety and efficacy of flow diversion for the treatment of PComA aneurysms with a meta‐analysis of the literature. Methods We performed a systematic search in Scopus, Embase, Medline, and Web of Science from inception until May 2022 for all the studies that reported the safety and effectiveness of FD for the treatment of intracranial aneurysms located in the posterior communicating artery. The primary effectiveness endpoint was a complete aneurysm occlusion rate at final follow‐up. The primary safety endpoint was a composite measure of cumulative events that occurred during and after the procedure. Events included death and ischemic/hemorrhagic complications. Random‐effects meta‐analysis was used to calculate proportions. Statistical heterogeneity across studies was assessed with I2 statistics. Results A total of 13 studies with 397 patients harboring 403 aneurysms were included in our analysis. Mean age was 48 years and mean aneurysm size was 5.3 mm. Complete aneurysm occlusion at final follow‐up was 74% (95% CI 66–81%; I2 = 54%). The primary safety composite outcome was 5% (95% CI 3–9%; I2 = 0%). The mortality rate was 1% (95% CI 0–2%; I2 = 0%). Subgroup analysis showed that patients with a non‐fetal PComA had a higher rate (76%; 95% CI 62%‐86%; I2 = 53%) of complete aneurysm occlusion compared to those with a fetal PComA (36%; 95% CI 21%‐54%; I2 = 0%). Conclusions Our findings show that flow diversion for the treatment of aneurysms located in the PComA is effective and safe. However, the same treatment for aneurysms located in a fetal‐type PComA did not show the same efficacy profile suggesting that these cases might require an alternative treatment to achieve permanent occlusion rates.